Analisis Transformasi Hujan-Debit dengan Metode Hidrograf Satuan Sintetik untuk Penetapan Banjir Rancangan pada DAS Manggar Kecil - Vita Ayu Kusuma Dewi; Gilang Id'fi; Namiratus Syarifah (G-Tech: Jurnal Teknologi Terapan, 2024)
To control flooding in Manggar Kecil watershed, it’s required to design the Flood Control Building (Bendali). This is aligned with the Balikpapan City government program, but there is limitation of flood discharge data in Manggar Kecil river included in the main parameter for bendali planning. To solve the limitation discharge data, transformation analysis of rainfall data to discharge (rainfall-runoff) can be conducted to obtain the value flood discharge. Analysis could using synthetic unit hydrograph methods. Quantitative descriptive is applied in this research and data collection from secondary data. Results of data analysis for return periods 10 to100 years include the Nakayasu method in the range of 167.02 to 212.92 m³/second, the Synder-Alexeyev method in the range of 123.31 to 157.19 m³/second and the Limantara method in the range of 202.01 to 257.53 m³/second. The determination of design flood value uses maximum discharge value of Limantara method.